नेत्रलाल ‘अभागी’ को जीवनयात्रा र कृतित्व - Aryal, Rambha Kumari (Haimaprabha, 2025)
The present article analyzes the life and works of Netralal Abhagi, a poet of the progressive stream of Nepali literature, born in Dang district in 2001. Netralal, known by the nickname ’Abhagi’ in the political and literary field, has been involved in the teaching profession for a long time and is known in public life by the name ’Madsab’. Netralal has published two collections of poems. Moreover, various researchers have mentioned nine additional works of the poet, both original version and translation, but most of them have become inaccessible so far. This study has used necessary data from his published books, unpublished manuscripts, text books and dissertations written on his biography and work. The study has used analytical methods incorporating biographical, historical and interpretive methods. In conclusion, Netralal Abhagi’s literary journey is engulfed from his ideological awareness. His initial ideological inclination was influenced by traditional culture and conservative society and his association with communist movement. His literary works express the wishes to liberate the Nepalese people, and bitter satire against feudalism, broker-bureaucratic capitalism, expansionism, imperialism and hegemony. At last Netralal is the icon of awakening conscience of the contemporary Nepalese people that he spills through his literary works.